Recent Applications of Electrospun Nanofibrous Scaffold in Tissue Engineering. (9th February 2022) - Owida, Hamza Abu; Al-Nabulsi, Jamal I.; Alnaimat, Feras; Al-Ayyad, Muhammad; Turab, Nidal M.; Al Sharah, Ashraf; Shakur, Murad
Abstract : Tissue engineering is a relatively new area of research that combines medical, biological, and engineering fundamentals to create tissue-engineered constructs that regenerate, preserve, or slightly increase the functions of tissues. To create mature tissue, the extracellular matrix should be imitated by engineered structures, allow for oxygen and nutrient transmission, and release toxins during tissue repair. Numerous recent studies have been devoted to developing three-dimensional nanostructures for tissue engineering. One of the most effective of these methods is electrospinning. Numerous nanofibrous scaffolds have been constructed over the last few decades for tissue repair and restoration. The current review gives an overview of attempts to construct nanofibrous meshes as tissue-engineered scaffolds for various tissues such as bone, cartilage, cardiovascular, and skin tissues. Also, the current article addresses the recent improvements and difficulties in tissue regeneration using electrospinning.